2016
DOI: 10.1167/iovs.16-20119
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cerebrospinal Fluid Pressure Estimation Using Formulae Derived From Clinical Data

Abstract: PURPOSE. To evaluate a frequently used regression model and a new, modified regression model to estimate cerebrospinal fluid pressure (CSFP). METHODS. Datasets from the Beijing iCOP study from Tongren Hospital, Beijing, China, and the Mayo Clinic, Rochester, Minnesota, were tested in this retrospective, case-control study. An often-used regression model derived from the Beijing iCOP dataset, but without radiographic data, was used to predict CSFP by using demographic and physiologic data. A regression model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our studies as well as those of Fleischman [7] suggest that more differentiated cut-offs, taking into consideration both age, gender and BMI should be used. Fleischman and coworkers have, more recently, based on retrospective clinical data from the Mayo clinic as well as data from Xie and coworkers from Beijing, compared estimation of CSFOP using regression model derived formulae with measured CSFOP values [8,15]. Though these models in addition to age and BMI also included blood pressure, model performance was similar to our results.…”
Section: Discussionsupporting
confidence: 82%
“…Our studies as well as those of Fleischman [7] suggest that more differentiated cut-offs, taking into consideration both age, gender and BMI should be used. Fleischman and coworkers have, more recently, based on retrospective clinical data from the Mayo clinic as well as data from Xie and coworkers from Beijing, compared estimation of CSFOP using regression model derived formulae with measured CSFOP values [8,15]. Though these models in addition to age and BMI also included blood pressure, model performance was similar to our results.…”
Section: Discussionsupporting
confidence: 82%
“…Although the eCSFP correlated relatively well with measured CSFP values in a previous study, one must bear in mind that the eCSFP value were just rough approximations needing further validation. 38 In that context, it has also to be considered that the width of the orbital cerebrospinal fluid space was not taken into account, since it was not feasible to measure it in a large community-based investigation. Since a wider orbital cerebrospinal fluid space is associated with higher CSFP and has also been taken as a surrogate for CSFP, one may think however that the parameter of CSFP already contains the orbital cerebrospinal fluid space width as parameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were troubled by the methodology employed by the study team. While we appreciate the mention of our study 2 that had found that formulae used to predict CSFP derived from clinical data were unable to accurately estimate CSF pressures, we were surprised that this formula was nonetheless used in the current study.…”
Section: Dear Editormentioning
confidence: 79%